On the Solar Wind Proton Temperature Anisotropy at Mars' Orbital Location. Issue 10 (27th September 2021) - Lentz, C. L.; Chasapis, A.; Qudsi, R. A.; Halekas, J.; Maruca, B. A.; Andersson, L.; Baker, D. N.
Abstract: The Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft can act as an intermittent upstream solar wind monitor at ∼ 1.5 AU. To inspect the evolution of solar wind turbulence in the Martian exosphere, we have gathered proton (i.e., ionized hydrogen) temperature measurements taken by the Solar Wind Ion Analyzer (SWIA) onboard the MAVEN spacecraft. Here we investigate instabilities driven by the proton temperature anisotropy at Mars during southern hemisphere fall, winter, spring, and summer seasons. We look at the relationship between the temperature anisotropy, R p = T ⊥ p / T ‖ p (i.e., the ratio of the perpendicular proton temperature component to the parallel proton temperature component), and the parallel plasma beta, β ‖ p, to determine any constraints imposed by kinetic instabilities. Furthermore, we report on the properties of turbulence near Mars' orbital location during upstream solar wind intervals from January 2015 to December 2016 ( ∼ 1 Martian year). We find that the probability distributions of ( β ‖ p, R p )‐values become limited when R p deviates greatly from unity. We also find evidence of intermittency implying nonlinear, non‐homogeneous energy transfer. Additionally, spectral indices obtained from basic fittings of power spectral densities of magnetic field fluctuations demonstrate a power law decay for inertial ranges ( 1 0 − 4 Hz to 0.1 Hz). Plain Language Summary: Radially emanating from the Sun, solar wind consists of highly ionized and strongly magnetized plasma. During its expansion, the solar wind develops into a turbulent flow. With increasing distance from the Sun, one would expect the temperature of protons in the solar wind to decrease at a certain rate. Instead, we see that protons are hotter than expected, and therefore some heating mechanism must be at work. One such mechanism can be turbulence. The energy of turbulent motions is converted into heat at small, proton gyroradius‐sized scales. This can cause the proton temperature components to become unequal when measured along axes in different directions, known as the proton temperature anisotropy. While there have been multiple spacecraft to characterize turbulence and proton temperature anisotropies at 1 AU, there exist limited opportunities to obtain these same measurements beyond this orbital location. To study the basic properties of turbulence and proton temperature anisotropies at Mars' orbital location, we used the Mars Atmosphere and Volatile EvolutioN spacecraft. Key Points: Microinstabilities play a role in limiting proton temperature anisotropy (both T ⊥ p T ‖ p > 1 and T ⊥ p T ‖ p < 1 ) upstream of Mars Probability density functions of magnetic field fluctuations exhibit intermittent structures present in upstream plasma at Mars Spectral indices obtained from power spectral densities of magnetic field fluctuations demonstrated a power law decay for inertial ranges